The Influence of Flexible Working Hours, Work-Life Balance, and Compensation on Gen Z - Purnamasari, Weny; Setiyani, Aris; Sofiati, Nunung Ayu; Sudaryo, Yoyo (Research Horizon, 2025)
Amid rapidly evolving workplace dynamics, job satisfaction and motivation have become pivotal in shaping employee productivity and loyalty, forming the foundation of this study’s investigation. This study aims to analyze the influence of flexible working hours, work-life balance, and compensations on employee satisfaction, with employee motivation serving as a mediating variable specifically among Generation Z employees in the manufacturing and service sectors in Bandung. A quantitative approach was applied using descriptive and verification methods. Data were collected through questionnaires distributed to 200 purposively selected respondents. The results indicate that the implementation of the three independent variables remains suboptimal, with average scores falling below the “good” category. Notably, flexible working hours and compensations showed a direct negative impact on both motivation and job satisfaction. Conversely, work-life balance had a strong positive effect on both variables. An interesting finding emerged when employee motivation was tested as a mediating variable: in some cases, motivation weakened the positive impact on satisfaction, suggesting a possible misalignment between the type of motivation provided and Generation Z’s internal expectations. This study highlights the urgent need for HR strategies that are responsive and aligned with Gen Z values and preferences to sustainably enhance employee satisfaction.